Caracterização estrutural por espectrometria de massas e cristalografia de raios X de lectinas da família Leguminosae - Rocha, Bruno Anderson Matias da (2007)
Although lectins from Leguminosae family were so well studies, sequences of Diocleinae sub tribe lectins have been shown that the circular permutation of peptide chains do not occur in some legume lectins. In addition, there are few structural data about Mimosoideae lectins, resulting in a difficulty structural classification of them [...]